Transforming Religious Pedagogy: The Implementation of Inquiry-Based Learning in Aqidah Akhlak Instruction - Ade Ayu Nur Fadillah (Sufiya Journal of Islamic Studies, 2023)
This study investigates the transformation of religious pedagogy through the implementation of inquiry-based learning in the teaching of Aqidah Akhlak. The study addresses the persistent issues of rote memorization and passive learning in madrasahs, which frequently fail to cultivate critical moral reasoning. Employing a qualitative descriptive approach, data were collected at a junior high school (Madrasah Tsanawiyah) in North Sumatra through interviews with subject teachers and field observations. The findings demonstrate that although students initially encountered difficulties with hypothesis formulation and data analysis, consistent procedural inquiry stimulated significant cognitive engagement and reflective thinking. The study identifies teacher competence and evocative stimulation as crucial catalysts, while cognitive disparities among students serve as a primary barrier. Theoretically, this research proposes that inquiry-based learning reactualizes the Islamic tradition of critical reasoning (ijtihad), bridging the gap between theological dogma and modern constructivist education. The results suggest that fostering an "inquisitive soul" is essential for developing a resilient religious identity within a contemporary context.